Effective, Secure and Robust CDMA Digital Image Watermarking in YCbCr Channel Using DWT2 - Khalili, Mehdi; Asatryan , David G. (Mathematical Problems of Computer Science, 2021)
Digital watermarking has been widely used in digital rights management and copyright protection. In this paper, a new cryptographic CDMA watermark scheme is proposed. Compared to the existing watermarking techniques, this proposed watermarking scheme combine transparency, security and robustness that none of the existing schemes can do. In this paper, a wavelet-based watermarking approach for hiding watermark image in color host images is proposed. The experimental results show that the proposed approach provides extra imperceptibility, security and robustness against JPEG compression and different noise attacks such as Gaussian and “Salt & Pepper” compared to the similar proposed methods such as [7]. Moreover, the proposed approach has no need of the original image to extract watermarks.